An innovative design of household civil defence shelters - Khong, Zhi Cong. (2010)
Civil Defence Shelter (CDS) is designed and constructed for the protection of people against emergency cases, such as the threads of potential war and terrorism. CDS should be able to protect its residents from weapon effects such as projectiles and bomb fragments. Current design depended heavily on sand as a material to make concrete for the CDS. In order to be less dependent on foreign imports for raw materials, there is a need to come up with alternatives to reduce the amount of sand needed. Two alternative designs for the CDS wall were proposed by previous Final Year Project (FYP) students. One is a composite wall made from welded I-section which forms a hollow steel section that is filled with recycled concrete aggregate (CRA). Another is a CDS with walls that are 40 percent leaner than the existing design. This was made possible by wrapping fibre polymer onto the surface of the wall. Two aspects related to the hollow steel section filled with RCA design were further studied. The effects of RCA size and the presents of grout were studied with respect to their penetration resistance. Penetration tests using gas gun were carried out on the discrete and bonded RCA to determine their penetration resistance. The samples were created and subjected to three levels of projectile pressure and their behaviour documented with attention being paid particularly to the depth of penetration. Conclusion was then drawn based on their penetration depth, style of impact and the aftermath condition of the projectile.